2021
DOI: 10.1093/cercor/bhab287
|View full text |Cite
|
Sign up to set email alerts
|

Commonalities and Asymmetries in the Neurobiological Infrastructure for Language Production and Comprehension

Abstract: The neurobiology of sentence production has been largely understudied compared to the neurobiology of sentence comprehension, due to difficulties with experimental control and motion-related artifacts in neuroimaging. We studied the neural response to constituents of increasing size and specifically focused on the similarities and differences in the production and comprehension of the same stimuli. Participants had to either produce or listen to stimuli in a gradient of constituent size based on a visual promp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
59
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(97 citation statements)
references
References 107 publications
11
59
2
Order By: Relevance
“…The simulated responses were generated using a linearly increasing temporal integration function (Figure 5a), based on prior work showing that information accumulation is accompanied by gradually increasing activation within phrases/sentences (Chang et al, 2020;Fedorenko et al, 2016;Giglio et al, 2021;Matchin et al, 2017;Nelson et al, 2017;Pallier et al, 2011) and paragraphs (Ezzyat & Davachi, 2011;Yarkoni et al, 2008) (a similar sentence/paragraph length effect was also observed in our data; see Figure S10). The linearly increasing temporal integration function accumulates activity within the interval between linguistic boundaries at given levels and flushes out the accumulated activity at linguistic boundaries.…”
Section: Simulating the Nested Narrative Structure That Drives The Lag Gradientmentioning
confidence: 54%
See 3 more Smart Citations
“…The simulated responses were generated using a linearly increasing temporal integration function (Figure 5a), based on prior work showing that information accumulation is accompanied by gradually increasing activation within phrases/sentences (Chang et al, 2020;Fedorenko et al, 2016;Giglio et al, 2021;Matchin et al, 2017;Nelson et al, 2017;Pallier et al, 2011) and paragraphs (Ezzyat & Davachi, 2011;Yarkoni et al, 2008) (a similar sentence/paragraph length effect was also observed in our data; see Figure S10). The linearly increasing temporal integration function accumulates activity within the interval between linguistic boundaries at given levels and flushes out the accumulated activity at linguistic boundaries.…”
Section: Simulating the Nested Narrative Structure That Drives The Lag Gradientmentioning
confidence: 54%
“…The simulated response amplitudes were generated using a linearly increasing temporal integration function (Fig. 4B), based on prior work showing that information accumulation is accompanied by gradually increasing activation within phrases/sentences (36)(37)(38)(39)(40)(41) and paragraphs (29, 32) (a similar sentence/paragraph length effect was also observed in our data; see SI Appendix, Fig. S12).…”
Section: Fig 4 Simulating Narrative Construction and The Correspondin...mentioning
confidence: 70%
See 2 more Smart Citations
“…However, these asymmetries may not necessarily reflect the separation between two distinct systems (Keenan, 1968;Tremblay & Dick, 2016;Chater, McCauley, & Christiansen, 2016). Furthermore, a growing body of research shows that the neural substrates underlying comprehension and production largely overlap (AbdulSabur et al, 2014;Giglio et al, 2021;Lukic et al, 2020;Silbert et al, 2014;Walenski et al, 2019), supporting the view that comprehension and production draw from processes and representations that are at least partially shared (Chater et al, 2016;Dell & Chang, 2014;Fairs et al, 2021;Gambi & Pickering, 2017;McQueen & Meyer, 2019;Pickering & Garrod, 2013).…”
Section: Introductionmentioning
confidence: 99%